اردو افسانے میں مذہب ، خدااور احترامِ انسانیت کے تصورات:پنڈت سدرشن کا خصوصی مطالعہ: Concepts of Religion, God and Respect for Humanity in Urdu Fiction: A Study of Pandit Sudarshan (Al-Qamar, 2018)
Religious beliefs have been the mainstay of Urdu literature. Genres of prose, such as stories, myths, plays, essays, critical essays, and general prose, as well as literary terms appear to be colored by the religious impression. This article explores the concepts of religion, God and respect for humanity in a well-known Indian writer Pandit Sudarshan's, fiction. ٰIt finds that Sudarshan has courteously depicted these concepts in his fiction. He emphasized respect for humanity and high moral values. He made the issues of rural and urban life, domestic affairs, confusions of individual and social lives, environmental complexity and class division the subject of his fiction. He unveiled the cruelty that arose as a result of the lust and luxury of the rich and capitalists. He showed the horrible face of the evil rich, which makes humanity tremble. His renowned collections "Chutkiyān", "Chandan", "Chashm-o-Chirāgh" etc. are a testament to this fact.
Keywords: Urdu fiction; religion; God; humanity; Pandit Sudarshan